2018
DOI: 10.3390/mi9060273
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Cochlear Sensory Epithelium with Functions of Outer Hair Cells Mimicked Using Feedback Electrical Stimuli

Abstract: We report a novel vibration control technique of an artificial auditory cochlear epithelium that mimics the function of outer hair cells in the organ of Corti. The proposed piezoelectric and trapezoidal membrane not only has the acoustic/electric conversion and frequency selectivity of the previous device developed mainly by one of the authors and colleagues, but also has a function to control local vibration according to sound stimuli. Vibration control is achieved by applying local electrical stimuli to patt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(44 citation statements)
references
References 38 publications
(59 reference statements)
3
39
0
Order By: Relevance
“…It is key that the device has a trapezoidal shape mimicking the basilar membrane and displays piezoelectric properties. It has been shown that a trapezoidal membrane [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] or an array of beams with various lengths [ 30 , 31 , 32 , 33 , 34 , 35 ] can realize frequency selectivity over a wide range of local resonance frequencies. Piezoelectric materials generate electrical signals in response to an external force making them applicable to fully implantable cochlear implants.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is key that the device has a trapezoidal shape mimicking the basilar membrane and displays piezoelectric properties. It has been shown that a trapezoidal membrane [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 ] or an array of beams with various lengths [ 30 , 31 , 32 , 33 , 34 , 35 ] can realize frequency selectivity over a wide range of local resonance frequencies. Piezoelectric materials generate electrical signals in response to an external force making them applicable to fully implantable cochlear implants.…”
Section: Introductionmentioning
confidence: 99%
“…Shintaku et al [ 36 ] have shown that poly(vinylidene fluoride–trifluoroethylene) (P(VDF-TrFE)) films are biocompatible and have low toxicity for the human body. In addition, polyvinylidene difluoride (PVDF) [ 22 , 23 , 25 , 29 , 33 , 35 ], lead zirconate titanate (PZT) [ 24 , 34 ], zinc oxide [ 26 ], and aluminum nitride [ 30 , 31 , 32 ] have also been applied in previous studies. Our and a few research groups have experimentally observed electrically evoked auditory brainstem responses (eABRs) with fully implantable artificial cochleae to evaluate their potential for clinical application [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations